Relationship between Asymmetry of Gait and Muscle Torque in Patients after Unilateral Transfemoral Amputation - Alicja Rutkowska-Kucharska; Mateusz Kowal; Sławomir Winiarski (Applied Bionics and Biomechanics)
Many studies have shown that unilateral transfemoral amputation involves asymmetric gait. Transfemoral amputation leads to muscle atrophy in a tight stump resulting in asymmetry in muscle torque between the amputated and intact limb. This research is aimed at verifying if a relationship between torque values of hip joint flexors and extensors and gait asymmetry in patients with TFA exists. Fourteen adult subjects with unilateral TFA took part in the experiment. Gait symmetry was evaluated based on the ground reaction force (GRF). Measurements of muscle torque of hip flexors and extensors were taken with a Biodex System. All measurements were taken under isokinetic (60°/s and 120°/s) and isometric conditions. The symmetry index of vertical GRF components was from 7.5 to 11.5%, and anterio-posterior GRF from 6.2 to 9.3%. The symmetry index for muscle torque was from 24.3 to 44% for flexors, from 39 to 50.5% for extensors, and from 28.6 to 50% in the flexor/extensor ratio. Gait asymmetry correlated with muscle torque in hip joint extensors. Therapy which enhances muscle torque may be an effective form of patient therapy. The patient needs to undergo evaluation of their muscle strength and have the therapy programme adjusted to their level of muscle torque deficit.